Implementasi Data Mining Menggunakan Algoritma C4.5 pada Klasifikasi Penjualan Hijab - Faridatul Husna; Hairur Rahman; Juhari Juhari (Jurnal Riset Mahasiswa Matematika, 2022)
Indonesia is known as a country with a majority Muslim population, this makes the need for clothing in Indonesia must also pay attention to the criteria for Muslim clothing, one of which is the hijab. Business developments in the fashion world, especially hijab, have become a trend setter at this time so that the large amount of data in the fashion business world creates conditions where there are businesspeople who have a lot of data but lack of information from that data. To deal with these conditions, it is necessary to classify the data. A classification is a process to find the same properties in a data set to be classified into different classes.  One of the classification methods is the Decision tree using the C4.5 Algorithm.  This research aims to determine the model and the accuracy of the C4.5 algorithm in classifying hijab sales from several hijab brands.  The Decision tree model is obtained using the C4.5 algorithm with the first root being the price attribute, where the first root is the attribute that most affected the sale of the hijab.  The result of calculating the accuracy value is 87% so that the Decision tree model and the classification process using the C4.5 Algorithm are classified as good. This research is expected to help businesspeople in the fashion sector, especially hijab, to find out the factors that influence consumer interest in a hijab product.